Purchasing Sebagai Titik Kritis Operasional Hotel: Studi Kualitatif Sistem Pengendalian Internal - Ni Made Sri Yadnya Wati; Ni Kadek Dewi Sukasih; Ni Nyoman Meita Jayantini (Politeknik Raflesia Press, 2026)
This study aims to analyse the implementation of internal control systems in the purchasing function at GN Resort Bali and identify gaps compared to the framework proposed by Mulyadi (2018). The purchasing function is considered a critical point in hotel operations due to its direct impact on cost efficiency, data reliability, and operational performance. This research uses a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The analysis compares actual practices with internal control principles, focusing on organizational structure, authorization procedures, and control practices. The results show that the internal control system in the purchasing function is not fully effective. The absence of segregation of duties, where purchasing, receiving, and storage functions are handled by the same unit, increases the risk of data manipulation and inefficiency. Additionally, the lack of an inventory system, where purchases are directly recorded as expenses, weakens control over material usage. The absence of standard operating procedures and supplier contracts further contributes to cost instability. This study concludes that purchasing is a critical operational point requiring stronger internal controls, including segregation of duties, SOP implementation, inventory systems, and improved monitoring. Keywords: purchasing, internal control, segregation of duties, hotel operations, cost control